Legal Protection Of Concurrent Creditors Due To Postponement of Debt Payment Obligations During The Covid-19 Pandemic - Adli, Muhammad; Eddy, Triono; Ramlan, Ramlan (Universitas Muhammadiyah Tangerang, 2024)
The rights of concurrent creditors in the decision to postpone debt payment obligations during the COVID-19 pandemic. To know and analyze the rights of concurrent creditors in determining the vote for extension and peace after the postponement of debt payment obligations during the COVID-19 pandemic. To find out and analyze the obstacles and legal protection efforts against concurrent creditors due to the postponement of debt payment obligations during the COVID-19 pandemic. Problem formulations for this journal are; How are the rights of concurrent creditors in the postponement of debt payment obligations during the Covid-19 pandemic?, How are the rights of concurrent creditors in determining the extension vote and peace after the postponement of debt payment obligations during the Covid-19 pandemic? and What are the obstacles and legal protection efforts against concurrent creditors due to the postponement of debt payment obligations during the COVID-19 pandemic? This research is normative legal research accompanied by supporting data. The research data was collected through a literature study. The analysis was carried out using qualitative methods. Based on the research results, it is concluded that: First, the rights of concurrent creditors in the decision to postpone debt payment obligations during the Covid-19 pandemic are based on the theory of positive law put forward by John Austin, namely in Article 222 paragraph (2) of Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. Second, The rights of concurrent creditors in determining the extension vote and peace after the postponement of debt payment obligations during the Covid-19 pandemic. Third, Obstacles to legal protection of concurrent creditors due to the postponement of debt payment obligations during the Covid-19 pandemic, namely the absence of funds for the costs of managing and administering postponement of debt payment obligations, uncooperative bankrupt debtors, and debtors selling/hiding their assets before being declared bankrupt. Legal protection efforts against concurrent creditors due to the decision to postpone debt payment obligations.Keywords: legal protection, concurrent creditors, postponement of debt payment obligations